KETASER01 protocol: What went right and what went wrong. Issue 3 (25th July 2022) - Rosati, Anna; L'Erario, Manuela; Bianchi, Roberto; Olivotto, Sara; Battaglia, Domenica Immacolata; Darra, Francesca; Biban, Paolo; Biggeri, Annibale; Catelan, Dolores; Danieli, Giacomo; Mondardini, Maria Cristina; Cordelli, Duccio Maria; et al.
Abstract: Objective: To discuss the results of the KETASER01 trial and the reasons for its failure, particularly in view of future studies. Methods: KETASER01 is a multicenter, randomized, controlled, open‐label, sequentially designed, non‐profit Italian study that aimed to assess the efficacy of ketamine compared with conventional anesthetics in the treatment of refractory convulsive status epilepticus (RCSE) in children. Results: During the 5‐year recruitment phase, a total of 76 RCSEs treated with third‐line therapy were observed in five of the 10 participating Centers; only 10 individuals (five for each study arm; five females, mean age 6.5 ± 6.3 years) were enrolled in the KETASER01 study. Two of the five patients (40%) in the experimental arm were successfully treated with ketamine and two of the five (40%) children in the control arm, where successfully treated with thiopental. In the remaining six (60%) enrolled patients, RCSE was not controlled by the randomized anesthetic(s). Significance: The KETASER01 study was prematurely halted due to low eligibility of patients and no successful recruitment. No conclusions can be drawn regarding the objectives of the study. Here, we discuss the KETASER01 results and critically analyze the reasons for its failure in view of future trials.